Wicked Problems in Architectural Research: The Role of Research by Design. Issue 1 (9th February 2022) - Pietrzyk, Krystyna
PhD students working in the field of architectural design often miss the reference to a consistent theoretical framework and a proper system of inquiry while working with the research design of their projects. Simultaneously, some of the architectural research questions and hypotheses are formulated as addressing wicked problems which causes methodological challenges. The aim of the paper is to put research by design approaches in the broader context of systems of inquiry and to emphasize their possible role to examine and resolve wicked problems. The paper first reviews some of the underlying assumptions of architectural research versus the assumptions behind different research paradigms characteristic for other fields. Then, the approaches and the methods in architectural research relevant to the chosen ontological, epistemological, and axiological assumptions are discussed. The theory of wicked problems is recalled as a relevant one for the complex, uncertain, projective tasks of architectural research. Research by design is seen as a method suitable for the investigation of wicked problems. It can reduce the epistemic uncertainty. Approaches of research by design are becoming more acknowledged in third cycle education in architecture. Two examples of recent PhD theses are briefly discussed in the paper in relation to the wicked aspects of their research/design problems, the research paradigm adopted and the role of research by design methodology. More conscious delineations and elaborations of a proper system of inquiry and the conscious use of research by design methodology can help in developing academic rigor of research studies addressing complex societal challenges.